Perchlorate in the Environment 2000
DOI: 10.1007/978-1-4615-4303-9_13
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Perchlorate from Waters Using Ion-Exchange Resins

Abstract: has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer. The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction. In the unlikel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 12 publications
1
63
0
Order By: Relevance
“…Unfortunately, liquid-phase mass spectrometric methods are often hindered by ion-suppression and ion-enhancement effects, where nontarget species interfere with accurate quantification. To obtain accurate quantitation using IC-MS or LC-MS techniques, many investigators used cleanup techniques to minimize interfering compounds (21) or standard addition to compensate for suppression/enhancement artifacts (36,37,41).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, liquid-phase mass spectrometric methods are often hindered by ion-suppression and ion-enhancement effects, where nontarget species interfere with accurate quantification. To obtain accurate quantitation using IC-MS or LC-MS techniques, many investigators used cleanup techniques to minimize interfering compounds (21) or standard addition to compensate for suppression/enhancement artifacts (36,37,41).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, a combination of selective ion exchange and the FeCl 3 -HCl regeneration technologies are promising in remediating groundwater contaminated with ClO 4 -with both a greatly increased treatment efficiency as well as a reduced frequency of resin regeneration compared to the waste brine production and disposal of conventional non-selective ion-exchange -(or about 100,000 bed volumes of water containing 50 µg/L ClO 4 -) (Gu et al, 2000a), the waste regenerant production is estimated to be <0.005% of the amount of groundwater treated. This is approximately 2 orders of magnitude less than what may be produced by using conventional NaCl brine regeneration technique (Batista et al, 2000;Brown et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…These resins are called "bifunctional" anionexchange resins because they have two quaternary ammonium groups: the first has long alkyl chains for higher selectivity, and the second has shorter alkyl chains for improved reaction kinetics. Treatment by ion exchange using these highly-selective anion exchange resins is one of the most promising methods for removing ClO 4 -at low concentration levels (Gu et al, 2000a,b;Brown et al, 2000;Bonnesen et al, 2000;Venkatesh et al, 2000;Tripp and Clifford, 2000;Batista et al, 2000). In addition to successful benchscale demonstrations, a recent field experiment showed that one bifunctional resin bed (Purolite D-3696) was able to treat more than 100,000 bed volumes of groundwater before a significant breakthrough of ClO 4 -occurred (with an initial ClO 4 -concentration of ~50 µg/L) (Gu et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Ion-exchange technology has been widely used for various separation processes, such as industrial processing of semi-conductors, water softening, and wastewater and groundwater treatment (Batista et al 2000, Tripp and Clifford 2000, Helfferich 1995, Melis et al 1996, Marina et al 1996, Tao and Xiao 1996, Sorg et al 1999, and Guseva et al 1988. The ion-exchange mechanism is generally known as being the result of simple electrostatic interaction, although factors such as the size and nature of counter-ions, their hydration energy, and the types of functional groups on resin surfaces significantly impact the thermodynamics and kinetics of the exchange reactions (Moyer and Bonnesen 1997, Gu et al 2000b.…”
Section: Ion Exchange Resinmentioning
confidence: 99%